COMPOSITION OF A LITERARY TEXT.THE MAIN THEME, IDEA,PLOT AND CONFLICT.CHARACTER CREATION AND CHARACTERIZATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article comprehensively analyzes the structural mechanics of literary text composition, detailing the interconnected roles of theme, idea, plot, conflict, and characterization. By evaluating qualitative narrative frameworks, it provides an academic model for modern literary analysis. (34 words)
Keywords: Literary composition, theme, narrative idea, plot dynamics, dramatic conflict, character creation, characterization methods, structural philology.